Enhancing Farmers' Insurance Literacy: Key To Improving AUTP Accessibility in Aceh Province - Liston Siringo Ringo; Hermanto Siregar; Nunung Kusnadi; Harianto Harianto (Jurnal Manajemen dan Agribisnis, 2025)
Background: Insurance literacy is crucial in improving farmers' access to insurance. Lack of understanding of insurance products and inability to process information hinder farmers from making the right decisions, resulting in low insurance utilization.Purpose: This research aims to (1) analyze farmers' insurance literacy levels and influencing factors and (2) analyze the effect of farmer insurance literacy and other variables on the accessibility of AUTP.Design/methodology/approach: Data from 251 respondents, including those who accessed and did not access AUTP in Aceh Province. To elucidate the research objectives, an analysis of the level of insurance literacy was conducted using multiple regression analysis and an analysis of accessibility to AUTP using binary logistic regression.Findings/Result: The results show that the level of farmer insurance literacy is in the less literate category. The variables of age, education duration, and bank account ownership significantly affect farmer insurance literacy. The variables that affect AUTP accessibility are age, education duration, farm revenue, land ownership, farmer insurance literacy value, farmer group activity, perception of farm risk, insurance claim experience, and AUTP premiums. These results can describe the condition of farmer insurance literacy and AUTP access in other regions of Indonesia with similar farmer characteristics.Conclusion: Farmers' insurance literacy has a significant impact on AUTP access. Therefore, the government and stakeholders need to conduct regular socialization and training to increase farmers' knowledge and awareness of insurance so that more farmers can take advantage of the AUTP program.Originality/value (State of the art): This study focuses on farmer insurance literacy. This study links farmer insurance literacy with AUTP access. Keywords: accessibility, Aceh, AUTP, insurance literacy, farmers